2019
DOI: 10.1177/1526602819872154
|View full text |Cite
|
Sign up to set email alerts
|

Mortality After Paclitaxel-Coated Device Use in Dialysis Access: A Systematic Review and Meta-Analysis

Abstract: Purpose: To report the risk of all-cause mortality in patients who underwent dialysis access treatment using paclitaxel-coated devices compared with percutaneous transluminal angioplasty (PTA) with an uncoated balloon. Materials and Methods: A systematic review and meta-analysis of randomized controlled trials were performed to investigate the mortality outcomes associated with paclitaxel-coated devices in the treatment of patients with a failing dialysis access (last search date February 28, 2019). The primar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 45 publications
1
42
0
Order By: Relevance
“…Patients who suffer from ESRD have a high risk of death and also a high chance of repeated interventions. Regarding DCB angioplasty of hemodialysis vascular access, a recent meta-analysis showed that there was no increase in mortality rate for up to 2 years [26]. Further studies are needed to investigate the long-term safety within this high-risk population.…”
Section: Safetymentioning
confidence: 99%
“…Patients who suffer from ESRD have a high risk of death and also a high chance of repeated interventions. Regarding DCB angioplasty of hemodialysis vascular access, a recent meta-analysis showed that there was no increase in mortality rate for up to 2 years [26]. Further studies are needed to investigate the long-term safety within this high-risk population.…”
Section: Safetymentioning
confidence: 99%
“…With primary and assisted primary access circuit patencies of 44% and 78%, our results are comparable to those obtained following the use of other methods of endovascular salvage. Finally, a recent study conducted by Dinh et al [26] showed no increased risk for all-cause mortality in patients treated with DEB angioplasty compared to those treated with PTA for dialysis access dysfunction during short-term and mid-term follow up.…”
Section: Discussionmentioning
confidence: 99%
“…A recent review drew attention to a possible increase in late mortality in patients undergoing DBA for peripheral arterial disease ( 37 ). However, the first meta-analysis investigating mortality following DCB use in the treatment of dysfunctional dialysis access circuits found no increased risk of all-cause mortality following DBA as compared to PBA at short- and mid-term follow-up ( 38 ).…”
Section: Discussionmentioning
confidence: 99%